Racial/Ethnic differences in emergency department triage assignment among visits for substance use. - Samantha Goldfarb; Natalie Dix; Austin Spitz; Katelyn Graves; Megan Deichen Hansen; Shermeeka Hogans-Mathews; Jessica Day; Jeffrey Harman (PLoS ONE)
Background The opioid/substance use disorder (SUD) epidemic in the United States has become a public health crisis. Stigma by health care workers towards patients with SUD has been identified as a barrier to treatment. Additionally, racial inequities in wait times and service provision have been found in Emergency Departments (EDs). Objective The purpose of this study was to examine the racial/ethnic differences in severity of ED triage assignment among visits for SUD. Methods This retrospective study utilized pooled data from the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 2016-20. The dependent variable was the recorded triage level for patients with SUD. The independent variable was patient race/ethnicity. Analyses controlled for variables such as age, sex, and arrival by ambulance. Differences in triage level by race/ethnicity among visits by patients with SUD was assessed via multivariable logistic regression models. Results Of the reported 788 SUD-specific ED visits from patients with SUD, 56.0% were non-Hispanic White, 28.6% were non-Hispanic Black, 12.9% were Hispanic, and 2.5% were of another race. Visits by Black patients with SUD had 53% lower odds of being assigned to an immediate/emergent triage level compared to visits by White patients with SUD (OR=0.47, p = .025). Conclusion We found that visits by Black patients with SUD were associated with lower odds of receiving an immediate/emergent triage assignment compared to visits by White patients with SUD, after adjusting for confounding variables. Our results suggest potential dual stigma in ED care of being Black and having a substance use disorder.